Cardiorespiratory Response to Exercise Among Undergraduate Students of Ghana and Nigeria - Akameze, Joy; Asante, Drusilla Obenewa; Eli-Cophie, Divine; Nti, Helena; Appiah Kusi, Frank; Oladele, Oladipo; Omotayo, Oluwaseun (Universitas Majalengka, 2024)
The purpose of this study was to compare dynamic aerobic cardiorespiratory response to exercise among undergraduate students of the Department of Sports and Exercise Medical Sciences, University of Health and Allied Sciences, Ghana and undergraduate students of the Department of Human Kinetics and Health Education of University of Calabar, Nigeria. Ex-post facto research design was adopted for the study. The Population consisted of undergraduate students of Ghana and Nigeria totalling 85 students. Simple random sampling technique was applied to select 50 participants (25 students from each country comprising 15 males and 10 females) for the study. Standardized instrument was used for data collection. The variables compared were Resting Heart Rate, Exercise heart Rate and Maximal Oxygen Consumption (VO2max). Data collected were subjected to descriptive and inferential statistics, where Independent t – test was applied to test for Hypotheses. The level of significance was set at .05 with 48 degree-of-freedom. The findings of the study revealed no significance differences in all the variables compared among the students of both Departments from both Countries, as a result the null hypotheses were rejected. It was concluded that the students from both Departments of the two different Countries in a related area of discipline exhibited good cardiorespiratory health and aerobic fitness as these are good indicator of physiological fitness for them to undertake their course in both Sports & Exercise Medical Sciences and Human Kinetics both in theory and in practice.